Anti-friction and anti-wear lubricating oil and preparation method thereof
By oxidizing and modifying carbon nanotubes and loading zinc oxide nanoparticles by sol-gel method, the problem of insufficient dispersion and stability of carbon nanotubes in lubricating oil is solved, and efficient wear resistance of lubricating oil is achieved Friction reduction performance and self-healing effect.
Patent Information
- Application Number
- CN202411627385.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
AI Technical Summary
After adding carbon nanotubes to existing lubricants, the dispersion and stability are insufficient, resulting in poor friction reduction and wear resistance and cannot meet the requirements of industrial applications.
By oxidizing the carbon nanotubes and modifying dodecyl triethoxysilane, modified carbon nanotubes loaded with zinc oxide nanoparticles are formed, and the loading is carried by the sol-gel method to enhance their lubricating oil dispersion and synergy in.
It significantly improves the anti-wear and friction-reducing performance of lubricating oil, and forms a film layer with good anti-wear and friction-reducing performance, which has self-healing effect and meets the requirements of industrial applications.
Smart Images

Figure BDA0005135084940000101 
Figure BDA0005135084940000111 
Figure BDA0005135084940000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oils, and in particular to a friction-reducing and anti-wear lubricating oil and a preparation method thereof. Background Art
[0002] Lubricating oil is a liquid or semi-solid lubricant used in various types of automobiles and mechanical equipment to reduce friction and protect machinery and processed parts. It mainly plays the role of lubrication, auxiliary cooling, rust prevention, cleaning, sealing and buffering. Simply put, it is between two relatively moving objects and has the function of reducing the friction caused by contact between the two objects.
[0003] In industrial production and daily life, lubricating oil is usually used to reduce friction and wear on materials or equipment. In order to increase the anti-friction and anti-wear properties of lubricating oil and improve the performance of lubricating oil, carbon nanotubes are usually added to lubricating oil to enhance its anti-wear properties. However, due to the microstructure of carbon nanotubes themselves and the easy adsorption characteristics of nanomaterials themselves, their dispersion and stability problems have not been effectively solved. Most of the current solutions are to treat the surface of carbon nanotubes by dispersants, surface modification, etc., but due to the unsatisfactory dispersion effect of their own characteristics, they cannot meet industrial applications.
[0004] For example, CN106367182A discloses a lubricating oil containing a carbon nanotube antiwear agent and a preparation method thereof, which belongs to the field of lubricating oil additives and includes the following components in mass percentage: 0.01-5% carbon nanotube antiwear agent, 0.01-2% dispersant, and 0.01-1% emulsifier, wherein the carbon nanotube antiwear agent is multi-walled carbon nanotubes prepared by ball milling.
[0005] For example, CN114015491B discloses a lubricating oil additive containing modified nano-carbon material, comprising 0.5-10wt% of modified nano-carbon material and 90-99.5wt% of additives by mass fraction; the additives include: 1-5wt% of ceramic phase powder, 50-90wt% of dispersant, 0-10wt% of detergent, 0-10wt% of anti-foaming agent, 1-5wt% of extreme pressure and anti-wear agent, 0.1-5wt% of oiliness agent and 0.1-5wt% of viscosity index improver. The modified nano-carbon material is a modified carbon nanotube.
[0006] However, the carbon nanotubes in the above patents have weak dispersibility, weak anti-wear and friction reduction capabilities, and weak stability of the modified carbon nanotubes. In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a friction-reducing and anti-wear lubricating oil and a preparation method thereof in order to overcome the poor friction-reducing and anti-wear performance of the above-mentioned prior art. The lubricating oil obtained by the present invention has excellent friction-reducing and anti-wear performance.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] The present application provides a friction-reducing and anti-wear lubricating oil, comprising, by weight, 70-90 parts of base oil, 10-20 parts of friction moderator, 1-5 parts of extreme pressure agent, 1-5 parts of detergent dispersant, 1-5 parts of pour point depressant, 1-5 parts of viscosity coefficient improver, 1-5 parts of defoamer, and 1-5 parts of antioxidant;
[0010] Wherein, the friction moderator is modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0011] Preferably, the preparation method of the friction moderator is:
[0012] S1, mixing dodecyltriethoxysilane with water, ethanol and isopropanol, and stirring to obtain a dispersion;
[0013] S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, stirring and reacting at 80-120° C. for 4-8 hours, adding the dispersion in S1, then refluxing at 100-150° C. for 1-3 hours, filtering and drying to obtain modified carbon nanotubes;
[0014] S3, mixing the modified carbon nanotubes, water, and zinc acetate and ultrasonicating for 15-40 minutes, then adding sodium hydroxide aqueous solution, reacting for 1-4 hours, and then ultrasonicating the liquid phase for 30-90 minutes, followed by centrifugal washing, collecting the solidified material and drying it at 60-100°C for 4-8 hours, and finally grinding to obtain the modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0015] Preferably, in step S1, the volume ratio of dodecyltriethoxysilane dissolved in water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1);
[0016] And / or, in step S2, the ratio of the carbon nanotubes, nitric acid and sulfuric acid is 1g:(50-100ml):(150-300ml);
[0017] And / or, in step S3, the ratio of the modified carbon nanotubes, water, and zinc acetate is 1g: (50-150ml): (2-3g), and the amount of sodium hydroxide is 1-3 times that of zinc acetate.
[0018] Preferably, the base oil comprises one of mineral oil or synthetic oil;
[0019] And / or, the viscosity index of the base oil is 80 to 120;
[0020] And / or, the extreme pressure agent includes one or more of phosphate extreme pressure agents, phosphite extreme pressure agents, acid phosphate extreme pressure agents, acid phosphite extreme pressure agents, dithiophosphoric acid extreme pressure agents, monothiophosphate extreme pressure agents, dithiophosphoric acid extreme pressure agents, chlorinated hydrocarbon extreme pressure agents, and organic metal extreme pressure agents;
[0021] and / or, the detergent dispersant includes one or more of metal sulfonates, metal salicylates, metal phenolates, organic phosphites, organic phosphates, metal organic phosphates, succinimide, benzylamine, succinates, and polyol esters;
[0022] And / or, the pour point depressant comprises polymethacrylate, and the weight average molecular weight of the polymethacrylate is 50,000-150,000;
[0023] and / or, the viscosity coefficient improver is preferably a polyisocyanate viscosity index improver;
[0024] And / or, the defoaming agent includes one or more of an organosilicon-based defoaming agent, a fluorine-based defoaming agent such as fluorosilicone oil and fluoroalkyl ether, and a polyacrylate-based defoaming agent.
[0025] The present application also provides a method for preparing a friction-reducing and anti-wear lubricating oil, comprising the following steps:
[0026] Base oil, friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoamer, antioxidant are mixed and added into a dissolving kettle, and the temperature is raised by heat transfer oil until the raw materials are completely dissolved and then stirred at a constant temperature. Meanwhile, the materials in the dissolving kettle are circulated by a pump and flow through a pipeline shearer at a high speed for shearing to obtain lubricating oil;
[0027] Wherein, the friction moderator is modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0028] Preferably, the preparation method of the friction moderator is:
[0029] S1, mixing dodecyltriethoxysilane with water, ethanol and isopropanol, and stirring to obtain a dispersion;
[0030] S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, stirring and reacting at 80-120° C. for 4-8 hours, adding the dispersion in S1, then refluxing at 100-150° C. for 1-3 hours, filtering and drying to obtain modified carbon nanotubes;
[0031] S3, mixing the modified carbon nanotubes, water, and zinc acetate and ultrasonicating for 15-40 minutes, then adding sodium hydroxide aqueous solution, reacting for 1-4 hours, and then ultrasonicating the liquid phase for 30-90 minutes, followed by centrifugal washing, collecting the solidified material and drying it at 60-100°C for 4-8 hours, and finally grinding to obtain the modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0032] Preferably, in step S1, the volume ratio of dodecyltriethoxysilane dissolved in water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1);
[0033] And / or, in step S2, the ratio of the carbon nanotubes, nitric acid and sulfuric acid is 1g:(50-100ml):(150-300ml);
[0034] And / or, in step S3, the ratio of the modified carbon nanotubes, water, and zinc acetate is 1g: (50-150ml): (2-3g), and the amount of sodium hydroxide is 1-3 times that of zinc acetate.
[0035] Preferably, the ratio of the amount of the base oil friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoamer and antioxidant is (70-90): (10-20): (1-5): (1-5): (1-5): (1-5): (1-5): (1-5);
[0036] and / or, when heating with heat transfer oil, the temperature is raised to 150-170° C.;
[0037] And / or, during shearing, the shearing time is 1 to 3 hours and the shearing temperature is 40 to 60°C.
[0038] Preferably, the base oil comprises one of mineral oil or synthetic oil;
[0039] And / or, the viscosity index of the base oil is 80 to 120;
[0040] And / or, the extreme pressure agent includes one or more of phosphate extreme pressure agents, phosphite extreme pressure agents, acid phosphate extreme pressure agents, acid phosphite extreme pressure agents, dithiophosphoric acid extreme pressure agents, monothiophosphate extreme pressure agents, dithiophosphoric acid extreme pressure agents, chlorinated hydrocarbon extreme pressure agents, and organic metal extreme pressure agents;
[0041] and / or, the detergent dispersant includes one or more of metal sulfonates, metal salicylates, metal phenolates, organic phosphites, organic phosphates, metal organic phosphates, succinimide, benzylamine, succinates, and polyol esters;
[0042] And / or, the pour point depressant comprises polymethacrylate, and the weight average molecular weight of the polymethacrylate is 50,000-150,000;
[0043] and / or, the viscosity coefficient improver is preferably a polyisocyanate viscosity index improver;
[0044] And / or, the defoaming agent includes one or more of an organosilicon-based defoaming agent, a fluorine-based defoaming agent such as fluorosilicone oil and fluoroalkyl ether, and a polyacrylate-based defoaming agent.
[0045] The present invention further provides a friction-reducing and anti-wear lubricating oil obtained by the above-mentioned method for preparing the friction-reducing and anti-wear lubricating oil.
[0046] Compared with the prior art, the present invention firstly performs oxidation treatment on the carbon nanotubes, and the carbon nanotubes are acidified by the action of sulfuric acid and nitric acid, and the large-scale appearance of hydroxyl and carboxyl groups on the outer surface is more conducive to modification, and on the other hand, impurities of the carbon nanotubes are also removed. In addition, the carbon nanotubes are modified by dodecyltriethoxysilane, and the hydroxyl groups on the surface of the carbon nanotubes react with silane for modification, and the hydrolysis and condensation of the silane groups will produce a cross-linked network structure, which is more conducive to loading nano zinc oxide particles, and the steric hindrance effect produced by dodecane reduces the van der Waals force, and the reason why the carbon nanotubes are easy to agglomerate and have poor dispersibility is its unique van der Waals force. The steric hindrance effect of dodecane is used to reduce the van der Waals force, which naturally enhances the dispersibility of the modified carbon nanotubes.
[0047] Then, the cross-linked grid structure generated on the surface of the modified carbon nanotubes is used to load nano zinc oxide. The nano zinc oxide particles are loaded by the sol-gel method to avoid organic solvents or corresponding high-temperature annealing treatment, thereby preventing the grid structure of the modified carbon nanotubes from being destroyed at high temperatures. The synthesis is simple and easy to repeat. The obtained modified carbon nanotubes loaded with zinc oxide nanoparticles, on the one hand, avoid the easy sedimentation and dispersion of zinc oxide added alone in the lubricating oil, and on the other hand, the nano zinc oxide and the modified carbon nanotubes synergistically improve the friction reduction and anti-wear effect of the lubricating oil.
[0048] When in use, the formulation of the present invention reacts with the surface of the lubricated object, such as a steel ball, to form a film layer with good anti-wear and friction-reducing properties, and the cross-linked grid distribution of the nano zinc oxide particles on the surface of the carbon nanotubes forms layers of anti-wear and friction-reducing film layers. This layered structure is easy to be oriented during the relative sliding of the friction pairs, and the movement between the friction pairs is converted into interlayer slippage inside the additive, which reduces friction resistance, improves the friction reduction and anti-wear properties of the lubricating oil, and even achieves a certain self-repairing effect, so that the anti-wear and friction-reducing properties are significantly improved. DETAILED DESCRIPTION
[0049] For ease of understanding of the present application, the present application will be described more fully below by way of embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0050] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0052] In order to increase the anti-friction and anti-wear properties of lubricating oil and improve its performance, carbon nanotubes are usually added to lubricating oil to enhance its anti-wear properties. However, due to the microstructure of carbon nanotubes and the easy adsorption characteristics of nanomaterials, their dispersion and stability problems have not been effectively solved. Most of the current solutions are to treat the surface of carbon nanotubes by dispersants, surface modification, etc., but due to their own characteristics, the dispersion effect is not ideal and the stability is not strong, which cannot meet industrial applications.
[0053] Based on this, the first aspect of the embodiment of the present application provides a friction-reducing and anti-wear lubricating oil, including 70-90 parts by weight of base oil, 10-20 parts of friction moderator, 1-5 parts of extreme pressure agent, 1-5 parts of detergent dispersant, 1-5 parts of pour point depressant, 1-5 parts of viscosity coefficient improver, 1-5 parts of defoaming agent, and 1-5 parts of antioxidant;
[0054] The friction moderator is modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0055] In an optional embodiment, the friction moderator is prepared by:
[0056] S1, dissolving dodecyltriethoxysilane in water and ethanol, wherein the volume ratio of dodecyltriethoxysilane, water, and ethanol is 1:(0.5-1):(0.5-1), preferably, the mass ratio of dodecyltriethoxysilane, water, and ethanol is 1:0.5:0.5, then adding isopropanol, the added volume of isopropanol is the same as the added amount of ethanol, and stirring to obtain a dispersion.
[0057] S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, wherein the ratio of carbon nanotubes, nitric acid and sulfuric acid is 1g:(50-100ml):(150-300ml), preferably 1g:50ml:150ml, stirring and reacting at 80-120°C for 4-8h, then adding the dispersion in S1, then refluxing at 100-150°C for 1-3h, preferably 2h, filtering and drying to obtain modified carbon nanotubes;
[0058] S3, mix modified carbon nanotubes, water, and zinc acetate and ultrasonicate for 15-40 minutes, wherein the ratio of modified carbon nanotubes, water, and zinc acetate is 1g: (50-150ml): (2-3g), preferably 1g: 100ml: 2.5g, then add sodium hydroxide aqueous solution, wherein the amount of sodium hydroxide is 1-3 times that of zinc acetate, react for 1-4h, then ultrasonicate the liquid phase for 30-90min, then centrifuge and wash, collect the solidified material and dry it at 60-100°C for 4-8h, preferably at 80°C for 6h, and finally grind to obtain modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0059] In this embodiment, the carbon nanotubes are firstly subjected to oxidation treatment, and the carbon nanotubes are acidified by the action of sulfuric acid and nitric acid, and the large-scale appearance of hydroxyl and carboxyl groups on the outer surface is more conducive to modification, and on the other hand, the impurities of the carbon nanotubes are also removed. In addition, by modifying the carbon nanotubes with dodecyltriethoxysilane, the hydroxyl groups on the surface of the carbon nanotubes react with silane for modification, and the hydrolysis and condensation of the silane groups will produce a cross-linked network structure, which is more conducive to loading nano zinc oxide particles, and the steric hindrance effect produced by dodecane reduces the van der Waals force, and the reason why carbon nanotubes are easy to agglomerate and have poor dispersibility is their unique van der Waals force. The steric hindrance effect of dodecane is used to reduce the van der Waals force, which naturally enhances the dispersibility of the modified carbon nanotubes.
[0060] Then, the cross-linked grid structure generated on the surface of the modified carbon nanotubes is used to load nano zinc oxide. The nano zinc oxide particles are loaded by the sol-gel method to avoid organic solvents or corresponding high-temperature annealing treatment, thereby preventing the grid structure of the modified carbon nanotubes from being destroyed at high temperatures. The synthesis is simple and easy to repeat. The obtained modified carbon nanotubes loaded with zinc oxide nanoparticles, on the one hand, avoid the easy sedimentation and dispersion of zinc oxide added alone in the lubricating oil, and on the other hand, the nano zinc oxide and the modified carbon nanotubes synergistically improve the friction reduction and anti-wear effect of the lubricating oil.
[0061] In an optional embodiment, the base oil includes mineral oil or synthetic oil, or a mixture of mineral oil and synthetic oil. Furthermore, the base oil can be selected from a viscosity index of 80 to 120, and more preferably 100.
[0062] In an optional embodiment, the extreme pressure agent includes one or more of phosphate extreme pressure agents, phosphite extreme pressure agents, acid phosphate extreme pressure agents, acid phosphite extreme pressure agents, dithiophosphoric acid extreme pressure agents, monothiophosphate extreme pressure agents, dithiophosphoric acid extreme pressure agents, chlorinated hydrocarbon extreme pressure agents, and organometallic extreme pressure agents.
[0063] In an optional embodiment, the extreme pressure agent is preferably dithiophosphoric acid.
[0064] In an optional embodiment, the detergent dispersant includes one or more of metal sulfonates, metal salicylates, metal phenolates, organic phosphites, organic phosphates, organic metal phosphates, succinimide, benzylamine, succinic acid esters, and polyol esters.
[0065] In an optional embodiment, the detergent dispersant is preferably sodium sulfonate.
[0066] In an optional embodiment, the pour point depressant comprises polymethacrylate.
[0067] In an optional embodiment, the weight average molecular weight of the polymethacrylate is preferably 50,000-150,000.
[0068] In an optional embodiment, the viscosity coefficient improver includes one or more of hydrogenated styrene diene copolymer and polyisobutylene.
[0069] In an optional embodiment, the viscosity coefficient improver is preferably a polyisocyanate viscosity index improver.
[0070] In an optional embodiment, the defoaming agent includes one or more of a silicone-based defoaming agent, a fluorine-based defoaming agent such as fluorosilicone oil and fluoroalkyl ether, and a polyacrylate-based defoaming agent.
[0071] In an optional embodiment, the defoaming agent is a silicone-based defoaming agent having a resin component concentration of 1% by mass.
[0072] In an optional embodiment, the antioxidant is one or more of a phenolic antioxidant, an amine antioxidant, a phenolic ester antioxidant and a thiophenolic ester antioxidant.
[0073] In an optional embodiment, the antioxidant is preferably an alkylated diphenylamine antioxidant.
[0074] The second aspect of the present application provides a method for preparing a friction-reducing and anti-wear lubricating oil, comprising the following steps:
[0075] Base oil, friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoamer, antioxidant are mixed and added into a dissolving kettle, and the temperature is raised by heat transfer oil until the raw materials are completely dissolved and then stirred at a constant temperature. Meanwhile, the materials in the dissolving kettle are circulated by a pump and flow through a pipeline shearer at a high speed for shearing to obtain lubricating oil;
[0076] Wherein, the friction moderator is modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0077] In an optional embodiment, the friction moderator is prepared by:
[0078] S1, dissolving dodecyltriethoxysilane in water and ethanol, wherein the volume ratio of dodecyltriethoxysilane, water, and ethanol is 1:(0.5-1):(0.5-1), preferably, the volume ratio of dodecyltriethoxysilane, water, and ethanol is 1:0.5:0.5, then adding isopropanol, the added volume of isopropanol is the same as the added amount of ethanol, and stirring to obtain a dispersion.
[0079] S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, wherein the ratio of carbon nanotubes, nitric acid and sulfuric acid is 1g:(50-100ml):(150-300ml), preferably 1g:50ml:150ml, stirring and reacting at 80-120°C for 4-8h, then adding the dispersion in S1, then refluxing at 100-150°C for 1-3h, preferably 2h, filtering and drying to obtain modified carbon nanotubes;
[0080] S3, mix modified carbon nanotubes, water, and zinc acetate and ultrasonicate for 15-40 minutes, wherein the ratio of modified carbon nanotubes, water, and zinc acetate is 1g: (50-150ml): (2-3g), preferably 1g: 100ml: 2.5g, then add sodium hydroxide aqueous solution, wherein the amount of sodium hydroxide is 1-3 times that of zinc acetate, react for 1-4h, then ultrasonicate the liquid phase for 30-90min, then centrifuge and wash, collect the solidified material and dry it at 60-100°C for 4-8h, preferably at 80°C for 6h, and finally grind to obtain modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0081] In an optional embodiment, the ratio of the base oil friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoaming agent, and antioxidant is (70-90): (10-20): (1-5): (1-5): (1-5): (1-5): (1-5): (1-5): (1-5).
[0082] In an optional embodiment, when the temperature is increased by heat transfer oil, the temperature is increased to 150-170°C, preferably 155-165°C, and more preferably 160°C; when shearing, the shearing time is 1-3h, preferably 1-2h, and more preferably 2h, and the shearing temperature is 40-60°C, preferably 50-60°C.
[0083] In an optional embodiment, the base oil includes mineral oil or synthetic oil, or a mixture of mineral oil and synthetic oil. Furthermore, the base oil can be selected from a viscosity index of 80 to 120, and more preferably 100.
[0084] In an optional embodiment, the extreme pressure agent includes one or more of phosphate extreme pressure agents, phosphite extreme pressure agents, acid phosphate extreme pressure agents, acid phosphite extreme pressure agents, dithiophosphoric acid extreme pressure agents, monothiophosphate extreme pressure agents, dithiophosphoric acid extreme pressure agents, chlorinated hydrocarbon extreme pressure agents, and organometallic extreme pressure agents.
[0085] In an optional embodiment, the extreme pressure agent is preferably dithiophosphoric acid.
[0086] In an optional embodiment, the detergent dispersant includes one or more of metal sulfonates, metal salicylates, metal phenolates, organic phosphites, organic phosphates, organic metal phosphates, succinimide, benzylamine, succinic acid esters, and polyol esters.
[0087] In an optional embodiment, the detergent dispersant is preferably sodium sulfonate.
[0088] In an optional embodiment, the pour point depressant comprises polymethacrylate.
[0089] In an optional embodiment, the weight average molecular weight of the polymethacrylate is preferably 50,000-150,000.
[0090] In an optional embodiment, the viscosity coefficient improver includes one or more of hydrogenated styrene diene copolymer and polyisobutylene.
[0091] In an optional embodiment, the viscosity coefficient improver is preferably a polyisocyanate viscosity index improver.
[0092] In an optional embodiment, the defoaming agent includes one or more of a silicone-based defoaming agent, a fluorine-based defoaming agent such as fluorosilicone oil and fluoroalkyl ether, and a polyacrylate-based defoaming agent.
[0093] In an optional embodiment, the defoaming agent is a silicone-based defoaming agent having a resin component concentration of 1% by mass.
[0094] In an optional embodiment, the antioxidant is one or more of a phenolic antioxidant, an amine antioxidant, a phenolic ester antioxidant and a thiophenolic ester antioxidant.
[0095] In an optional embodiment, the antioxidant is preferably an alkylated diphenylamine antioxidant.
[0096] A third aspect of the embodiments of the present application provides a friction-reducing and anti-wear lubricating oil obtained by the preparation method of the above-mentioned friction-reducing and anti-wear lubricating oil.
[0097] The above implementation is described in more detail below with reference to specific examples.
[0098] Preparation Example
[0099] Example 1
[0100] This embodiment provides a friction-reducing and anti-wear lubricating oil, comprising the following steps:
[0101] Base oil, friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoamer and antioxidant are mixed in proportion and added to a dissolving kettle, wherein the usage ratio of base oil, friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoamer and antioxidant is 70:15:3:3:3:3:2:1, and the temperature is raised to 160°C by heat transfer oil to completely dissolve the raw materials. After complete dissolution, constant temperature stirring is continued for 30 minutes. At the same time, the material in the dissolving kettle is circulated by a pump and flows through a pipeline shearer at high speed for shearing for 2 hours. The shearing temperature is 55°C, and finally lubricating oil is obtained.
[0102] The friction moderator is a modified carbon nanotube loaded with zinc oxide nanoparticles, and the preparation method thereof is as follows:
[0103] S1, dissolving dodecyltriethoxysilane in water and ethanol, wherein the volume ratio of dodecyltriethoxysilane, water, and ethanol is 1:0.5:0.5, then adding isopropanol, the added volume of isopropanol is the same as the added amount of ethanol, and stirring to obtain a dispersion.
[0104] S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, wherein the ratio of carbon nanotubes, nitric acid and sulfuric acid is preferably 1g:50ml:150ml, stirring and reacting at 100°C for 6h, then adding the dispersion in S1, then refluxing at 120°C for 2h, filtering and drying to obtain modified carbon nanotubes;
[0105] S3, mixed modified carbon nanotubes, water, and zinc acetate and ultrasonicated for 30 minutes, wherein the ratio of modified carbon nanotubes, water, and zinc acetate is 1g:100ml:2.5g, then added sodium hydroxide aqueous solution, wherein the amount of sodium hydroxide is twice that of zinc acetate, reacted for 2 hours, then ultrasonicated the liquid phase for 60 minutes, then centrifuged and washed, collected the solidified material and dried it at 80°C for 6 hours, and finally ground to obtain modified carbon nanotubes loaded with zinc oxide nanoparticles.
[0106] The base oil is a mineral oil with a viscosity coefficient of 100, the extreme pressure agent is dithiophosphoric acid, the detergent dispersant is sodium sulfonate, the pour point depressant is polymethacrylate, the weight average molecular weight of the polymethacrylate is 100,000, the viscosity coefficient improver is a polyisocyanate viscosity index improver, the defoamer is a silicone defoamer with a resin component concentration of 1% by mass, and the antioxidant is an alkylated diphenylamine antioxidant.
[0107] Example 2
[0108] Compared with Example 1, most of the contents are the same, except that the weight parts of the raw materials are changed to those shown in Table 1 below.
[0109] Table 1
[0110] Components Weight Base oil 75 Friction reducer 10 Extreme Pressure Agents 3 Detergents and dispersants 3 Pour Point Depressant 3 Viscosity improver 3 Defoaming agent 2 Antioxidants 1
[0111] Example 3
[0112] Compared with Example 1, most of the contents are the same, except that the weight parts of the raw materials are changed to those shown in Table 2 below.
[0113] Table 2
[0114]
[0115]
[0116] Example 4
[0117] Compared with Example 1, most of the contents are the same, except that the weight parts of the raw materials are changed to those shown in Table 3 below.
[0118] Table 3
[0119] Components Weight Base oil 70 Friction reducer 15 Extreme Pressure Agents 3 Detergents and dispersants 3 Pour Point Depressant 2 Viscosity improver 3 Defoaming agent 3 Antioxidants 1
[0120] Comparative Example 1
[0121] Compared with Example 1, most of the contents are the same, except that the weight parts of the raw materials are changed as shown in Table 4 below.
[0122] Table 4
[0123]
[0124]
[0125] Comparative Example 2
[0126] Compared with Example 1, most of them are the same, except that the friction moderator is changed to the following:
[0127] S1, dissolving dodecyltriethoxysilane in water and ethanol, wherein the volume ratio of dodecyltriethoxysilane, water, and ethanol is 1:0.5:0.5, then adding isopropanol, the added volume of isopropanol is the same as the added amount of ethanol, and stirring to obtain a dispersion.
[0128] S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, wherein the ratio of carbon nanotubes, nitric acid and sulfuric acid is preferably 1g:50ml:150ml, stirring and reacting at 100°C for 6h, then adding the dispersion in S1, and then refluxing at 120°C for 2h, filtering and drying to obtain modified carbon nanotubes.
[0129] Comparative Example 3
[0130] Compared with Example 1, most of them are the same, except that the friction moderator is changed to nano zinc oxide.
[0131] Comparative Example 4
[0132] Compared with Example 1, most of the above are the same, except that the friction moderator is changed to a mixture of nano zinc oxide and modified carbon nanotubes in a weight ratio of 1:1, wherein the modified nanotubes are prepared in the following manner:
[0133] S1, dissolving dodecyltriethoxysilane in water and ethanol, wherein the volume ratio of dodecyltriethoxysilane, water, and ethanol is 1:0.5:0.5, then adding isopropanol, the added volume of isopropanol is the same as the added amount of ethanol, and stirring to obtain a dispersion.
[0134] S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, wherein the ratio of carbon nanotubes, nitric acid and sulfuric acid is preferably 1g:50ml:150ml, stirring and reacting at 100°C for 6h, then adding the dispersion in S1, and then refluxing at 120°C for 2h, filtering and drying to obtain modified carbon nanotubes.
[0135] Test example
[0136] The maximum non-seizure load of each sample was measured according to GB / T3142 lubricating oil load capacity determination method (four-ball method), the anti-wear performance of each sample was measured according to SH / T0189 lubricating oil anti-wear performance determination method (four-ball machine method), and the anti-wear performance of lubricating oil was measured according to SH / T0188 method. The test conditions were: oil temperature 54°C, load 1335N, running time 60min, and high-frequency reciprocating test machine (HFRR) was used to measure the friction coefficient. The test conditions were: frequency 20HZ, temperature 50°C, load 400g, time 60min. The results are shown in Table 5 below.
[0137] Table 5
[0138] Examples Maximum no-seizure load / N Wear spot diameter / mm Weight loss / mg Friction coefficient Example 1 967 0.42 15.6 0.078 Example 2 989 0.41 15.1 0.071 Example 3 961 0.42 15.7 0.081 Example 4 956 0.43 15.8 0.082 Comparative Example 1 563 0.62 23.6 0.121 Comparative Example 2 724 0.59 19.2 0.115 Comparative Example 3 621 0.69 21.1 0.118 Comparative Example 4 784 0.56 18.5 0.112
[0139] It can be seen from Table 5 above that the formulation of the present application has excellent anti-wear and friction-reducing properties compared to the formulation shown in the comparative example.
[0140] Among them, compared with Example 1, Comparative Example 1 does not add friction moderator, and its anti-wear and friction reduction performance is poor. Compared with Example 1, Comparative Example 2 only adds modified carbon nanotubes, and its anti-wear and friction reduction performance is better than Comparative Example 1 and Comparative Example 3, which shows that the modified carbon nanotubes are significantly helpful in improving the anti-wear and friction reduction performance. Compared with Example 1, Comparative Example 3 only adds nano zinc oxide, and its anti-wear and friction reduction performance is better than Comparative Example 1, which shows that the addition of nano zinc oxide can improve the anti-wear and friction reduction performance. Compared with Example 1, Comparative Example 4 adds modified carbon nanotubes and nano zinc oxide. Although the anti-wear and friction reduction performance is improved, it is still not as good as the formula of the present application, which shows that the sol-gel method used in the present application can significantly improve the synergistic effect of modified carbon nanotubes and nano zinc oxide.
[0141] The formula of this application firstly performs oxidation treatment on carbon nanotubes, and the carbon nanotubes are acidified by the action of sulfuric acid and nitric acid, and the large-scale appearance of hydroxyl and carboxyl groups on the outer surface is more conducive to modification, and on the other hand, impurities of carbon nanotubes are also removed. In addition, by modifying carbon nanotubes with dodecyltriethoxysilane, the hydroxyl groups on the surface of carbon nanotubes react with silane for modification, and the hydrolysis and condensation of silane groups will produce a cross-linked network structure, which is more conducive to loading nano zinc oxide particles, and the steric hindrance effect produced by dodecane reduces the van der Waals force, and the reason why carbon nanotubes are easy to agglomerate and have poor dispersibility is their unique van der Waals force. The steric hindrance effect of dodecane is used to reduce the van der Waals force, which naturally enhances the dispersibility of the modified carbon nanotubes.
[0142] Then, the cross-linked grid structure generated on the surface of the modified carbon nanotubes is used to load nano zinc oxide. The nano zinc oxide particles are loaded by the sol-gel method to avoid organic solvents or corresponding high-temperature annealing treatment, thereby preventing the grid structure of the modified carbon nanotubes from being destroyed at high temperatures. The synthesis is simple and easy to repeat. The obtained modified carbon nanotubes loaded with zinc oxide nanoparticles, on the one hand, avoid the easy sedimentation and dispersion of zinc oxide added alone in the lubricating oil, and on the other hand, the nano zinc oxide and the modified carbon nanotubes synergistically improve the friction reduction and anti-wear effect of the lubricating oil.
[0143] When in use, the formulation of the present application reacts with the surface of the lubricated object, such as a steel ball, to form a film layer with good anti-wear and friction-reducing properties, and the cross-linked grid distribution of the nano zinc oxide particles on the surface of the carbon nanotubes forms layers of anti-wear and friction-reducing film layers. This layered structure is easy to orient during the relative sliding of the friction pairs, and the movement between the friction pairs is transformed into interlayer slippage inside the additive, which reduces friction resistance, improves the friction reduction and anti-wear properties of the lubricant, and even achieves a certain self-repairing effect, which significantly improves the anti-wear and friction-reducing properties.
[0144] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A friction-reducing and anti-wear lubricating oil, characterized in that: The invention comprises 70-90 parts by weight of base oil, 10-20 parts of friction moderator, 1-5 parts of extreme pressure agent, 1-5 parts of detergent dispersant, 1-5 parts of pour point depressant, 1-5 parts of viscosity coefficient improver, 1-5 parts of defoamer and 1-5 parts of antioxidant; Wherein, the friction moderator is modified carbon nanotubes loaded with zinc oxide nanoparticles.
2. The anti-friction lubricating oil according to claim 1, characterized in that: The preparation method of the friction moderator is: S1, mixing dodecyltriethoxysilane with water, ethanol and isopropanol, and stirring to obtain a dispersion; S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, stirring and reacting at 80-120° C. for 4-8 hours, adding the dispersion in S1, then refluxing at 100-150° C. for 1-3 hours, filtering and drying to obtain modified carbon nanotubes; S3, mixing the modified carbon nanotubes, water, and zinc acetate and ultrasonicating for 15-40 minutes, then adding sodium hydroxide aqueous solution, reacting for 1-4 hours, and then ultrasonicating the liquid phase for 30-90 minutes, followed by centrifugal washing, collecting the solidified material and drying it at 60-100°C for 4-8 hours, and finally grinding to obtain the modified carbon nanotubes loaded with zinc oxide nanoparticles.
3. The anti-friction lubricating oil according to claim 2, characterized in that: In step S1, the volume ratio of dodecyltriethoxysilane dissolved in water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1); And / or, in step S2, the ratio of the carbon nanotubes, nitric acid and sulfuric acid is 1g:(50-100ml):(150-300ml); And / or, in step S3, the ratio of the modified carbon nanotubes, water, and zinc acetate is 1g: (50-150ml): (2-3g), and the amount of sodium hydroxide is 1-3 times that of zinc acetate.
4. The anti-friction lubricating oil according to claim 1, characterized in that: The base oil includes one of mineral oil or synthetic oil; And / or, the viscosity index of the base oil is 80 to 120; And / or, the extreme pressure agent includes one or more of phosphate extreme pressure agents, phosphite extreme pressure agents, acid phosphate extreme pressure agents, acid phosphite extreme pressure agents, dithiophosphoric acid extreme pressure agents, monothiophosphate extreme pressure agents, dithiophosphoric acid extreme pressure agents, chlorinated hydrocarbon extreme pressure agents, and organic metal extreme pressure agents; and / or, the detergent dispersant includes one or more of metal sulfonates, metal salicylates, metal phenolates, organic phosphites, organic phosphates, metal organic phosphates, succinimide, benzylamine, succinates, and polyol esters; And / or, the pour point depressant comprises polymethacrylate, and the weight average molecular weight of the polymethacrylate is 50,000-150,000; and / or, the viscosity coefficient improver is preferably a polyisocyanate viscosity index improver; And / or, the defoaming agent includes one or more of an organosilicon-based defoaming agent, a fluorine-based defoaming agent such as fluorosilicone oil and fluoroalkyl ether, and a polyacrylate-based defoaming agent.
5. A method for preparing a friction-reducing and anti-wear lubricating oil, characterized in that: The following steps are involved: Base oil, friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoamer, antioxidant are mixed and added into a dissolving kettle, and the temperature is raised by heat transfer oil until the raw materials are completely dissolved and then stirred at a constant temperature. Meanwhile, the materials in the dissolving kettle are circulated by a pump and flow through a pipeline shearer at a high speed for shearing to obtain lubricating oil; Wherein, the friction moderator is modified carbon nanotubes loaded with zinc oxide nanoparticles.
6. The method for preparing a friction-reducing and anti-wear lubricating oil according to claim 5, characterized in that: The preparation method of the friction moderator is: S1, mixing dodecyltriethoxysilane with water, ethanol and isopropanol, and stirring to obtain a dispersion; S2, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid, stirring and reacting at 80-120° C. for 4-8 hours, adding the dispersion in S1, then refluxing at 100-150° C. for 1-3 hours, filtering and drying to obtain modified carbon nanotubes; S3, mixing the modified carbon nanotubes, water, and zinc acetate and ultrasonicating for 15-40 minutes, then adding sodium hydroxide aqueous solution, reacting for 1-4 hours, and then ultrasonicating the liquid phase for 30-90 minutes, followed by centrifugal washing, collecting the solidified material and drying it at 60-100°C for 4-8 hours, and finally grinding to obtain the modified carbon nanotubes loaded with zinc oxide nanoparticles.
7. The anti-friction lubricating oil according to claim 6, characterized in that: In step S1, the volume ratio of dodecyltriethoxysilane dissolved in water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1); And / or, in step S2, the ratio of the carbon nanotubes, nitric acid and sulfuric acid is 1g:(50-100ml):(150-300ml); And / or, in step S3, the ratio of the modified carbon nanotubes, water, and zinc acetate is 1g: (50-150ml): (2-3g), and the amount of sodium hydroxide is 1-3 times that of zinc acetate.
8. The method for preparing a friction-reducing and anti-wear lubricating oil according to claim 5, characterized in that: The ratio of the base oil friction moderator, extreme pressure agent, detergent dispersant, pour point depressant, viscosity coefficient improver, defoamer and antioxidant is (70-90): (10-20): (1-5): (1-5): (1-5): (1-5): (1-5): (1-5); and / or, when heating with heat transfer oil, the temperature is raised to 150-170° C.; And / or, during shearing, the shearing time is 1 to 3 hours and the shearing temperature is 40 to 60°C.
9. The method for preparing a friction-reducing and anti-wear lubricating oil according to claim 5, characterized in that: The base oil includes one of mineral oil or synthetic oil; And / or, the viscosity index of the base oil is 80 to 120; And / or, the extreme pressure agent includes one or more of phosphate extreme pressure agents, phosphite extreme pressure agents, acid phosphate extreme pressure agents, acid phosphite extreme pressure agents, dithiophosphoric acid extreme pressure agents, monothiophosphate extreme pressure agents, dithiophosphoric acid extreme pressure agents, chlorinated hydrocarbon extreme pressure agents, and organic metal extreme pressure agents; and / or, the detergent dispersant includes one or more of metal sulfonates, metal salicylates, metal phenolates, organic phosphites, organic phosphates, metal organic phosphates, succinimide, benzylamine, succinates, and polyol esters; And / or, the pour point depressant comprises polymethacrylate, and the weight average molecular weight of the polymethacrylate is 50,000-150,000; and / or, the viscosity coefficient improver is preferably a polyisocyanate viscosity index improver; And / or, the defoaming agent includes one or more of an organosilicon-based defoaming agent, a fluorine-based defoaming agent such as fluorosilicone oil and fluoroalkyl ether, and a polyacrylate-based defoaming agent.
10. A friction-reducing and anti-wear lubricating oil obtained by the method for preparing the friction-reducing and anti-wear lubricating oil according to any one of claims 5 to 9.
Citation Information
Patent Citations
Lubricating oil containing carbon nanotube antiwear agent, and preparation method of lubricating oil
CN106367182A
A lubricating oil additive containing modified nano-carbon materials and its preparation method
CN114015491B